2021
DOI: 10.1111/jcpp.13412
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity during facial processing in autism spectrum disorder: an activation likelihood estimation (ALE) meta‐analysis of neuroimaging studies

Abstract: Background Though aberrant face processing is a hallmark of autistic spectrum disorder (ASD), findings on accompanying brain activity are divergent. Therefore, we conducted an activation likelihood estimation (ALE) meta‐analysis of studies examining brain activity during face processing. Methods We searched PubMed and PsycINFO using combinations of terms as ‘fMRI’, ‘Autism Spectrum Disorder’, ‘Face Perception’. Eligible studies reported on DSM‐diagnosed ASD individuals, compared to controls (HC), using face st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…It has previously been suggested that differences in social brain activations between ASD and NC could be contributed by a lack of preference towards social stimuli (Philip et al, 2012 ), which cannot be ruled out in our meta-analysis. These findings are in line with previous ASD functional neuroimaging meta-analyses, which have reported the left amygdala as one of the differentially activated regions during emotion and face processing (Aoki et al, 2015 ; Costa et al, 2021 ) and social cognition (Patriquin et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…It has previously been suggested that differences in social brain activations between ASD and NC could be contributed by a lack of preference towards social stimuli (Philip et al, 2012 ), which cannot be ruled out in our meta-analysis. These findings are in line with previous ASD functional neuroimaging meta-analyses, which have reported the left amygdala as one of the differentially activated regions during emotion and face processing (Aoki et al, 2015 ; Costa et al, 2021 ) and social cognition (Patriquin et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…Activation likelihood estimation (ALE) technique is a metaanalysis method that calculates the consistency of statistically important focal points in experiments based on the probability distribution centered on the coordinates of each set of focal points (Costa et al, 2021). This approach has significant implications for studies with inconsistent findings because it can theoretically analyze the most stable changes in brain activity (Goodkind et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The quality and risk of bias (RoB) of included studies were evaluated with a modified version of the Newcastle–Ottawa scale (mNOS), which adapted to fMRI data [ 11 ]. This version uses a different set of items adapted to fMRI studies [ 12 ]. Scores on the mNOS range from 0 to 11, with 0 to 3 considered indicative of high risk, 4 to 7 as intermediate, and 8 to 11 as low risk.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 1297 publications were retrieved from initial search, among which 37 studies met the inclusion criteria (654 participants in the SAD groups and 594 participants in the control groups). There were 15 studies that adopted emotional faces as task stimuli [12][13][14][15][16][17][18][19][20][21][22][23][24][25], 8 that presented specific situations as task stimuli [26][27][28][29][30][31][32][33], and the other 14 employed other types of tasks [5,[34][35][36][37][38][39][40][41][42][43][44][45][46]. In total, the coordinates where SAD groups…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%